The effect of two different weight-gain interventions on body composition and performance in elite athletes - Garthe, I.; Raastad, T.; Refsnes, P.; Sundgot-Borgen, J. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Because muscle mass is an important determinant of performance in sports dependent on high muscle strength or power (e.g. weight lifting, alpine skiing), there is a need for effective muscle mass gaining protocols. The most important factors promoting an increase in muscle mass is strength training combined with positive energy balance, and an increase in body mass of 0.25-0.5 kg per week may be possible depending on genetics and the resistance-training history of the athlete (1,2). For Elite athletes with heavy training loads, competitions and limited time for proper nutrition strategies, it can be a difficult task to increase lean body mass (LBM) or to maintain LBM during the competitive season. Thus, a significant number of these athletes are using excessive supplementation and diets high in saturated fat. Purpose: To evaluate the effect of nutritional guidance in a 10-12 weeks weight-gain period in elite athletes. Methods: 39 male and female elite athletes where randomized into two groups, "nutritional guidance group" (NG, n=21, 19.1±2.9 y, 70.9±8.9 kg) and "ad libitum group" (ALG, n=18, 19.6±2.7 y, 75.0±5.9kg). The Athletes in NG followed a strict meal plan based on a 4-day weighed food registration, providing a positive daily energy intake corresponding to 544±143 kcal whereas the athletes in the ALG had an ad libitum energy intake with no nutritional guidelines. All athletes continued their normal sport specific training (16.7±5.4h per week), and in addition all included four resistance-training sessions per week to emphasize muscle hypertrophy. Assessments done pre and post intervention were: body weight (BW), dual energy x-ray absorptiometry (DEXA), 1 RM tests (squat and bench press and bench pull). Results: The energy intake during the intervention period was significantly higher in the NG than in the ALG (3585±601 vs. 2964±884 kcal, respectively). BW increased with 3.9±0.6% in NG and 1.5±0.4% in ALG. Total LBM increased by 2.7±0.4% in the NG but was not significantly changed in the ALG (1.8±0.4%, p=0.6). There was larger increase in fat-mass in NG (14.7±3.7%) than in ALG (2.5±2.6%). Strength performance was improved in both the NG and ALG in 1 RM bench press (11.5±8.5% and 9.0±1.8%), in 1RM squat (9.1±1.4% and 11.5±2.0%) and in 1 RM bench pull (9.0±3.4% and 6.1±1.6%), respectively. Conclusion: In terms of reaching their weight-gain goals, the athletes in NG was significant more successful than the ALG. Due to long history of heavy strength-training, the athletes had limited possibilities to increase LBM and performance in these variables. For overall body composition goal, the excess energy intake in a weight-gain protocol should be considered carefully since greater rates of gain are likely to include increments in body fat storage in trained athletes.